SUSTAINABLE FINANCE: TRENDS, OPPORTUNITIES AND EMERGING CHALLENGES - D Radhika, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Sustainable finance is an emerging field that integrates Environmental, Social, and Governance (ESG) principles into financial decision-making. It focuses on generating long-term value rather than seeking immediate profit. This sector encompasses various financial activities, including green bonds, impact investing, and ESG-driven banking. These initiatives support projects in renewable energy, sustainable agriculture, and social welfare. As the global economy increasingly embraces sustainability, financial markets play a crucial role in linking investments to the Sustainable Development Goals (SDGs). This study examines the framework, classifications, emerging trends, challenges, and opportunities in sustainable finance. Despite the growing emphasis on sustainability, challenges such as market inefficiencies, the absence of standardized reporting, and the risk of greenwashing hinder the sector’s growth. Many investment opportunities remain untapped due to high transaction costs, insufficient data transparency, and inconsistent regulatory frameworks. However, advancements in green technologies, the expansion of the green bond market, and the integration of ESG factors into investment strategies present significant opportunities for investors and businesses. The adoption of standardized impact measures and enhanced financial accessibility through green microfinance can promote sustainable finance, drive long-term economic stability while address global environmental and social challenges.